2022
DOI: 10.1111/bjep.12524
|View full text |Cite
|
Sign up to set email alerts
|

This is the way: Network perspective on targets for spatial ability development programmes

Abstract: Background: Spatial ability (SA) was shown to be important for success in different fields, including STEM. Recent research suggested that SA is a unitary construct, rather than a set of related skills. However, it is not clear how individual differences in different facets of SA emerge, and how they relate to variance in general cognitive ability. Aims: The aim of the present study was threefold: 1) to examine the structure of SA testing nine theoretical models; 2) to explore the relation between 16 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 107 publications
(163 reference statements)
0
1
0
1
Order By: Relevance
“…In addition, there was also significant overlap between this factor and large-scale SA tasks (when the viewer's perspective can change with respect to the larger environment, but the spatial relationships among individual objects are fixed -e.g. wayfinding, navigation, orienting in space), as shown by M. Malanchini and colleagues, M. V. Likhanov and colleagues [35,36]. This data suggests that a small number of object-oriented SA tests can reasonably capture small-scale SA.…”
Section: Literature Reviewmentioning
confidence: 67%
“…In addition, there was also significant overlap between this factor and large-scale SA tasks (when the viewer's perspective can change with respect to the larger environment, but the spatial relationships among individual objects are fixed -e.g. wayfinding, navigation, orienting in space), as shown by M. Malanchini and colleagues, M. V. Likhanov and colleagues [35,36]. This data suggests that a small number of object-oriented SA tests can reasonably capture small-scale SA.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Кроме того, выбор стратегии зависит и от содержания самой задачи. В литературе продолжается дискуссия о том, являются ли пространственные способности Барцева К. В., Лиханов М. В., Солдатова Е. Л. М е ж д и с ц и п л и н а р н ы е и с с л е д о ва н и я к о г н и т и в н ы х п р о ц е с с о в однофакторным [9][10][11] или многофакторным [12][13][14] конструктом. Так, обсуждаются стратегии ментального вращения, навигации, пространственной визуализации, чтения карт и др., каждая из которых приблизительно соответствует определенному типу задачи.…”
Section: Introductionunclassified
“…Research has also suggested that SA can be differentially linked to verbal and spatial ability depending on the language [38][39][40][41] . For example, effects differed from 0.12 to 0.7 in the aforementioned studies as a function of the language.…”
mentioning
confidence: 99%